Review and analysis of demonstration projects on power-to-X pathways in the world. (22nd October 2019) - Chehade, Zaher; Mansilla, Christine; Lucchese, Paul; Hilliard, Samantha; Proost, Joris
Abstract: Transforming the energy system towards more sustainability can only be achieved through a combination of low-carbon energy, energy efficiency, and the coupling of energy sectors. In this context, the application of Power-to-Hydrogen concepts for managing demand, providing seasonal storage, and linking elements between different sectors has attracted significant interest during the last decade. Demonstration is a key first step towards large-scale market introduction. This paper presents the results of a review of 192 Power-to-X demo projects in 32 countries. Results show that the features of demonstrations have evolved significantly over the years: electrolysis capacity has increased, both for PEM and alkaline systems, and the potential for balancing and ancillary services is increasingly investigated via grid-connected demos. The scope of Hydrogen-to-X pathways has also evolved over the years, mainly to include industry applications. This work was carried out under the umbrella of Task 38 of the IEA Hydrogen Technology Collaboration Programme. Highlights: 192 Power-to-X demonstrations in 32 countries were identified. Results show that the investigated pathways diversified (towards industry recently). Balancing services are increasingly investigated via grid-connected demos.